Avaliação da percepção de notas musicais em adultos cegos - Medeiros, Paloma Cavalcante Bezerra de (2010)
This work aimed to evaluate if the lack of visual information can alter the perception of musical notes in blind adults when compared to adults with normal vision. The sample of this study was comprised of 30 adults (15 blinds (Experimental Group - EG) and 15 with normal vision (Control Group - CG)), 7 females and 8 males in each group from 18 to 30 years old, all with normal hearing acuity. All measurements were made by the forced-choice method between two alternatives. In this method, the volunteer had always to choose the certain stimulus informed previously by the experimenter (the test stimulus) between two stimuli. The other stimulus showed was a distracter stimulus. The measurements were made in 3 experimental sessions, one for each stimulus. In each experimental session, 20 pairs of stimuli were presented at random, one stimulus was the test stimulus and the other the distracter stimulus. The musical notes used as test stimulus were D, F and A in the first octave of the piano. The distracter stimulus were the musical notes that are neighboring the test note according to the standard musical notes scale (it means that when D was the test note, the distracter notes were C and E; to the F note, the distracters were E and G). Before the beginning of the experiment, the test stimulus of the session was presented for five consecutive times and the experiment only began when the experimenter was sure that the volunteer had understood all the instructions. The rate of discrimination (the number of rights divided per the number of presentations) for each musical note were gathered according to condition (CG and EG). The statistical analysis (One-Way ANOVA) did not show significant differences between the groups F (2, 27) = 2.17, p > 0.05 to discriminate musical notes. These results suggest that the congenital lack of vision do not cause changes in the ability to discriminate musical notes in blind adults.